FRI0338 Efficacy and safety of rituximab retreatment in refractory systemic juvenile idiopathic arthritis. (23rd January 2014) - Alexeeva, E.; Valiyeva, S.; Denisova, R.; Bzarova, T.; Isayeva, K.
Abstract : Background: Chimeric monoclonal anti-CD20 B-cell antibody (rituximab) is promising drug for the treatment of systemic Juvenile Idiopathic Arthritis (SJIA) refractory to immunosuppressive drugs and TNFα-blockers. Objectives: evaluate clinical efficacy and safety of rituximab retreatment in patients with SJIA. Methods: 75 patients were enrolled in the study, 36 boys and 39 girs with SJIA. Range of age was from 2, 3 to 17 years; mean disease duration was 5, 32 (0.6; 7, 0) years. Rituximab was administered at a mean dose of 375 mg/m 2 /administration according to the following regimen: 1 dose once a week for 4 consecutive weeks every 24 weeks. The next course of Rituximab was administrated if patients had systemic manifestations, active joints, increasing level of CRP and ESR in 24 weeks after Rituximab treatment. 75 patients have received one treatment course (24 weeks), 72 children have received 2 courses (48 weeks), 55 children have received 3 courses (72 weeks), 38 – 4 courses (96 weeks), 23 – 5 courses (120 weeks). Results: The ACR Pedi 30, 50, 70 were achieved by 85%, 45%, 40% of patients at Week 24 (n=75), and by 90%, 75%, 70% of patients at Week 48 (n=72), respectively. At week 72 (n=69) ACR pedi 50 and 70 were achieved by 75% and 70% of patients. The remission was achieved by 25% of patients at Week 24, by 48% of patients at Week 48, by 65% of patients at Week 72 and by 80% and 90% of patients at Week 96 (n=58) and 120 (n=52).Long-term adverse events included ENT infections, less frequently - skin infections, herpetic infection and pneumonia (in 9 children). Among these children, in 4 patients Pneumocystis was revealed, in 2 patients - Pneumocystis plus Mycoplasma, in 3 patients the causative agent was not identified. All children received antibacterial treatment. In 22 patients neutropenia was observed. Conclusions: Rituximab is effective drug of treatment in patients with SJIA.The remission was achieved by 90% of patients at Week 120. Disclosure of Interest: None Declared